Exploring transnational legal orders: using transnational environmental law to strengthen the global regulation of black carbon for the benefit of the Arctic region - Kati Kulovesi (Edward Elgar Publishing, 2020)
This illuminating Research Handbook offers a detailed overview and critical discussion of the key themes and perspectives that characterize the burgeoning research area of transnational environmental law. Varied perspectives from leading and emerging scholars are brought together to deliver methodological and conceptual frameworks for future research, whilst providing an original view on this emerging field of law.